Phases of Capitalist Development - Westra, Richard. author. aut Link
XIII, 352 p.
Keywords: In this collection authors from eight different countries, representing a wide variety of academic disciplines and theoretical perspectives, investigate the differing phases of capitalist development. They offer diverse and powerful analyses of the postwar boom, economic crises and globalization within this context.